Religieuse pluraliteit en waarheid: die hoofstroom Christelike respons - Louw, D. J. (Faculty of Theology, University of the Free State, 2005)
Our shrinking world confronts us with a plurality of religion of which all claim to be "true". How should we evaluate these claims? The mainstreean Christian response to this question oscillates beween exclusism and inclusivism. These responses are explained and evaluated with references to Karl Barth (conservative exclusivism), Hendrik Kraemer and Emil Brunner (liberal exclusivism) and Karl Rahner (inclusivism). It is concluded that the responses of both the exclusivist and inclusivist boil down to the very subjective arbitrariness that they wish to avoid.

Ons kleiner wordende wêreld konfronteer ons met 'n pluraliteit van godsdienste en 'n daamee korrelerende plurateit van aanprake op "waarheid". moet ons hierdie aansprake evalueer? Die atwoord wat die meente Christene op hiede vraag gee, ossiller tussen eksklivisme en insklusivisme. Hierdie standpunte word krities bespreek aan die han van Karl Barth (konserwatiewe eksklusivisme), Hendrik Kraemer en Emil Brunner (liberale ekslusivisme) en Karl Rahner (inklusivisme). Daar word tot die slotsom gekom dat die standpunt van sowel die eksklusivis as die inklusivis uiteindelik mank gaan aan die subjecktiewe willekeur wat hulle juis wou vermy.
Keywords: Religious pluralism; Truth; Exclusivism; Inclusivism